Primary Borderline Mucinous Testicular Tumor: A Case Report and Literature Review - Hao, Changjuan; Kang, Chunsong; Kang, Xiaoyan; Yu, Zhuanzhuan; Li, Tingting; Xue, Jiping (Frontiers in Oncology, 2021)
Primary mucinous tumors of the testis and paratestis are very rare, with only 29 reported cases detected in a PubMed search. The histopathological characteristics of primary testicular mucinous tumors are similar to their ovarian counterparts, and the diagnosis and naming criteria refer to the criteria for female ovarian mucinous tumors. However, the clinical and imaging features of primary testicular mucinous tumors are poorly understood, and they are thus frequently undiagnosed or misdiagnosed. We present the case of a patient with a primary testicular mucinous tumor. A 52-year-old man presented with a 1-year history of painless enlargement of the left scrotum. Ultrasound examination revealed a cystic mass in the left testis, with viscous fluid areas and calcified spots, irregular solid bulges on the cyst wall, and a small blood supply. Serum alpha-fetoprotein, β‐human chorionic gonadotropin, lactate dehydrogenase, renal function, inflammatory markers, and routine urine and blood examinations were all normal. The patient underwent radical resection of the left testis. Postoperative pathology showed a multilocular cystic mass, with the inner wall of the sac lined with mucous columnar epithelial cells, some with mild nuclear atypia, and no interstitial infiltration. The pathological diagnosis was testicular mucinous tumor. Postoperative abdominal and pelvic computed tomography, colonoscopy, and gastroscopy showed no suspicious lesions. The final diagnosis was primary testicular borderline mucinous tumor. The patient underwent postoperative follow-up examinations once a year for 4 years. Serum tumor markers, scrotal ultrasound, abdominal and pelvic computed tomography scans, and colonoscopy and gastroscopy revealed no evidence of metastases or other primary adenocarcinoma. This case highlights the clinical and imaging characteristics of primary testicular mucinous tumors, which might aid their differential diagnosis.